Relação da família com o processo de escolarização durante a pandemia: dificuldades encontradas - Mainente, Maria Jozelma Barbosa (2022)
The pandemic caused by COVID-19 has directly affected people's way of life. Society had to adapt to live with the virus and survive it. Over time, the pandemic limited social actions and several actions were sanctioned by public agencies. Among these, the closing of schools and the adoption of remote teaching in many Brazilian municipal areas. From this scenario, the present study aimed to analyze achievements, challenges and difficulties faced by families and students during the pandemic, to ensure access, participation and learning in remote classes. The theoreticalmethodological framework of this research is Socio-Historical Psychology. For its conduction, a qualitative method was chosen, with a reflective interview, with the participation of two mothers and a father of students enrolled in the 2nd year of Elementary School, in the year 2021, who experienced the pandemic in the first years of literacy, from a municipal school in the city of Santo André, state of São Paulo. The information collected in the interviews was analyzed using Content Analysis. Five categories were created for analysis and discussion. The results showed that the families interviewed organized themselves in the best possible way in an attempt to meet the pedagogical, physical, mental and affective needs of the students. However, if observed from the researcher's point of view as a teacher in the municipal network of Santo André, it was not unanimous that all families were able to adapt their routine during the pandemic, as many students remained away from the teaching-learning process, even in the face of the adoption of active search engines. Problems were reported and exposed that, if analyzed, have been present in Basic Education for years and have been accentuated with the pandemic scenario, such as failure rate, evasion, abandonment, age-grade distortion, year/grade gap and, above all, social inequalities. The importance and social function of the school and of the entire school community in the process of acquiring knowledge and human formation of the subject was evidenced, in addition to the need to invest in structuring and emergency public policies, which minimize the different inequalities existing in Brazil, wide open through the pandemic, ensuring the guarantee of the rights provided for the Brazilian Federal Constitution to all Brazilian citizens. It is considered necessary to carry out more research on the subject to identify the consequences of the lack of access caused by the pandemic and the measures adopted by governments to remedy them